Les communs fonciers à l’ère d’internet au Cambodge, une approche par les conflits - Marie Mellac; Jean-Christophe Diepart (Netcom)
Since the years 2000, political life in Cambodia has been deeply marked by land conflicts, brought about by the destruction of rural and urban commons. These conflicts occur in a context where violence and patronage, which are at the core of Cambodian State formation practises, limit approaches to counter power. However, spaces of resistance exist and are actively transformed by the internet. Through the prism of land conflicts, this article examines how different mobilizations of the Web bring an informational dimension to the social dynamics of protecting land-based commons. The release of land-related data and information on the internet by civil society actors shakes up the central role of the State as data gatekeeper. Yet, the link between these intervention on the Web and land governance is not obvious and remain to be explored.